Pengaruh IPM dan Pengangguran terhadap Pertumbuhan Ekonomi dalam Perspektif Islam di Provinsi Bengkulu - Fasmala Sari, Fina; Mursalin, Supardi; Putra Hasibuan, Rahmat (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This study aims to determine how the economic growth of Bengkulu Province is influenced by the unemployment rate and the Human Development Index (HDI) from an Islamic economic point of view. If HDI measures the quality of human resources in terms of living standards, education, and health, then unemployment shows how effective the use of labor in a field is. The time series of data from 2012 to 2023 obtained from the Bengkulu Province Central Bureau of Statistics (BPS) is the secondary data source in this study. The method applied is Mixed Method. Multiple linear regression is the test used to analyze, along with hypothesis testing and classical assumptions, to determine the extent to which independent factors affect the dependent variable. The results showed that HDI had a partially negative and significant impact on economic growth, but had no significant effect on the unemployment variable. Unemployment and HDI together have a major impact on the economic growth of Bengkulu Province in 2012-2023. Therefore, increasing and reducing HDI is considered an important effort to realize fair and sustainable economic growth according to sharia principles because from the point of view of Islamic economics, economic development is measured by considering material aspects as well as the balance between the needs of the world and the hereafter.